Counselling and Psychotherapy in Organisational Settings - Moore Judy; Roberts Ruth (Learning Matters, 2010)
This book is part of the Counselling and Psychotherapy Practice series written specifically to support students on Counselling and Psychotherapy courses. Series Editor's Preface, Acknowledgements, About the Contributors, Introduction, Counselling in Schools, Counselling in Further Education (FE) Colleges, Counselling in Higher Education (HE), Counselling in a Voluntary Agency, Addictions Counselling in a Residential Treatment Centre, Counselling and Psychotherapy in Prisons, Counselling in Occupational Health (OH) and Employee Assistance Programs (EAPs), Counselling within an IAPT Context, References, Index.